Challenges of implementation of new public management in public sectors: a study of kalmunai divisional secretariat of ampara district - Jabbar, M.A.; Fowsar, M.A.M. (University of Jaffna, 2012)
In the last quarter century there has been a significant shift within the field of Public Administration. One aspect of this trend has been the emergence of a concept which has come to be known as the New Public Management (NPM). At the most basic level, this concept promotes the public sector use of private sector management techniques. Due to number of pressures, NPM has spread across the world influencing a wide range of states. However, there are reservations over the general applicability of NPM, especially in the developing world. In this context, this paper outlines the rise of NPM in the context of Sri Lanka. Further addresses the issues in introducing NPM techniques in Divisional Secretariats of Sri Lanka, as a case of Kalmunai Divisional Secretariat which has established in the coastal area of Ampara District. This study is a critical one based on interpretative analysis which has used quantitative and qualitative data. The stated purpose of this study is examined by studying both primary and secondary materials. The primary data has been collected through questionnaire survey, key informants interviews and focus group discussion. The secondary data has been collected from books, official documents, reports and journals. The major findings of the study is that the above institution has been challenged in implementing the NPM techniques owing to various reasons including lack of knowledge, lack of staff capacity of the institution, etc.
Keywords: New public management; Public sectors and public administration